(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the impact of oral health on the quality of life and depression of independent elderly people. Methods: Systematic review of the literature outlined according to the PECO strategy with the question: Elderly (Population / Control) who have oral problems (Outcome) will have better / worse quality of life and depression (Exposure)? Results: Libraries and databases were used: Medline, Scopus, Web of Science, Lilacs and Cochrane Library, in a comprehensive and unrestricted manner to the year or language of publication. The MeSH terms used for search were: Elderly; Dental care for aged, Health services for the aged, Depression, Quality of life. After the search, 972 articles were identified, of which 197 were excluded after removing the duplicates and 689 for not answering the research question. After reading the abstracts, 6 articles were read in full and included in this review. Conclusion: Oral changes affect the quality of life and depression of independent elderly people.